Physiological Needs of the Main Character in the Novel Hello Cello by Nadia Ristivani: A Study of Abraham Maslow's Humanistic Psychology - Aulia Dwi Nawangsari; Resdianto Permata Raharjo (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the physiological needs of the main character in Nadia Ristivani’s novel Hello Cello. This study uses a qualitative descriptive method with a literary psychology approach. This study uses a research design consisting of identifying research problems, reviewing literature, selecting research objects, collecting data, and identifying research. The data source in this study is the novel Hello Cello by Nadia Ristivani, with data consisting of quotations, sentences, and paragraphs in accordance with the description of the fulfillment of the physiological needs of the main character based on Maslow’s humanistic psychology study. The data collection technique was carried out by reading and noting, including the steps of preparing, reading, sorting, recording, and coding the data. Data analysis used the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. The results show that Helga, as the main character, tries to fulfill five levels of needs, especially physiological needs, ranging from the need for food and drink, clothing, shelter, rest and sleep, and sexual needs. The fulfillment of these physiological needs became the basis for Helga to achieve balance in her life and recover from the emotional trauma caused by her failed relationship. Through the portrayal of Helga’s character, the novel Hello Cello emphasizes that psychological disorders can affect the fulfillment of basic human needs, and conversely, the fulfillment of physiological needs can be the first step towards emotional stability and self-actualization.